CAMPUR KODE BAHASA JEPANG OLEH PENUTUR BAHASA INDONESIA DI JEJARING SOSIAL FACEBOOK - Ernawati, Ni Luh (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 25 No 2 (2018): September, 2019)
Indonesian people who can speak Japanese language often mix elements of Japanese language when communicating with the people of Indonesia who is also able to speak Japanese languange either directly or on social networks like facebook. This linguistic phenomenon peeled sociolinguistic theory based on the concept of code mixing. The primary data source is utterances which was updated status and comments of Indonesian people that contain code mixing on facebook. The secondary data were obtained from the online interviews with several informants who their updated status or comments of facebook were used for the primary data source.The results of the data analysis showed that the type of code mixing of the Indonesian on facebook in terms of element uptake language used is outer code mixing, while in terms of system -level linguistic device are clauses code mixing, phrases code mixing, and words code mixing. The factors that influence the event of code mixing are (1) speaker wants to practice Japanese language that they learned; (2) there are some elements of Japanese language that can not be interpreted 100% to Indonesian language; (3) speaker is one community with the patner; (4) can provoke the patner to use Japaese language; (6) to be more cool (7) the things that was communicated was related to the Japan.